Development of biomarkers to detect the effects of organic pollution on aquatic invertebrates: recent molecular, genotoxic, cellular and immunological studies on the common mussel (Mytilus edulis L.) and other mytilids. (1st January 2000) - Livingstone, D.R.; Chipman, J.K.; Lowe, D.M.; Minier, C.; Pipe, R.K.
Organic contaminants are continually entering aquatic environments and thence the tissues of resident biota. Mussels and other molluscs are used worldwide as sentinels in pollution monitoring. Recent years have seen the development of biological measurements (biomarkers) as tools for use in monitoring and environmental impact assessment, such biomarkers being indicative of contaminant exposure and/or impact. This paper describes established and developmental biomarkers in mussels responsive to exposure to organic contaminants, including some indicative of damage to DNA ("comet" assay) putative induction of biotransformation enzymes (CYP1A-like protein), contaminant removal (MXR-like protein), lysosomal membrane damage and impairment of membrane function.